To understand the emerging Mexico: human rights, democracy and violence / Para entender al México emergente: derechos humanos, democracia y violencia - Samuel F. Velarde (Barataria, 2015)
Human Rights, democracy and violence have been in the past fifteen years the variables that concern in social analysis of Mexico, Mexican reality can’t be understood if the intersection of these variables and what causes the national context are not understood. This article addresses from a descriptive and analytical perspective, how each of these mentioned elements allows focusing and understanding of the current situation by which crosses the country and therefore display the sociopolitical future of the country in a century that seems complex and full of unpublished vicissitudes.